Las sanciones en materia tributaria en el Ecuador (Foro: Revista de Derecho, 2017)
El régimen sancionatorio en materia tributaria es manifestación del ius puniendi estatal, en el que discurre la sanción como la consecuencia de la realización de un supuesto de hecho calificado jurídicamente como infracción, de allí la pertinencia del análisis de esta figura que devele la naturaleza, fines, tipología y las competencias de los órganos administrativos y jurisdiccionales llamados a imponerla, con remisión constitucional y legal a la realidad ecuatoriana, que examine también los principios que informan a este régimen y a ser observados en los procedimientos e imposición de sanciones tributarias.The penalty system on tax matters is a manifestation of the state ius puniendi, in which sanctions, as the consequence of the assumptions made in the case legally qualified as an infringement, appear, thus the relevance of the analysis of this precept is to unveil its nature, purpose, type, and the competencies of the administrative bodies and courts called upon to impose it, with reference to the constitutional and legal situation in Ecuador, examining also the principles underlying this penalty system, and to be observed in proceedings and imposition of tax penalties.The penalty system on tax matters is a manifestation of the state ius puniendi, in which sanctions, as the consequence of the assumptions made in the case legally qualified as an infringement, appear, thus the relevance of the analysis of this precept is to unveil its nature, purpose, type, and the competencies of the administrative bodies and courts called upon to impose it, with reference to the constitutional and legal situation in Ecuador, examining also the principles underlying this penalty system, and to be observed in proceedings and imposition of tax penalties.